The Sinuosity of Rivers in Northern Finland - Mansikkaniemi,Hannu (1970)
The report develops a method to determine the sinuosity of rivers by which the following things are discovered: the amount of sinuosity (Si) as percentages, the quality of sinuosity (small sinuosity or river sinuosity, and great sinuosity or valley sinuosity) and how the sinuosity is distributed over different parts of the river. The rivers or their parts are classified on the basis of sinuosity to: very straight (Si < 20.0%), straight (20.0--29.9%), crooked (30.0--39.9%), sinuous (40.0--49.9%), and very sinuous (50.0% and more). 41 rivers in northern Finland were analyzed in this method. The straightest of these are the rivers discharging into the Arctic Ocean and the most sinuous are the rivers in the drainage area of the Kemijoki river. The sinuosity of rivers generally increases from the mouth to the upper course. The amount of sinuosity has no dependence e.g. on the gradient of the river but mainly on the topography of the crystalline bedrock in the investigated area. (Author)